THE RELATIONSHIP BETWEEN WORK VALUE SUPPORT AND SUBJECTIVE CAREER SUCCESS: THE ROLE OF CAREER COMMITMENT AS MEDIATOR - Syahrizal, Syahrizal; Marisaa, Poetri (Jurnal Mebis, 2023)
This study aims to examine the relationship between work value support, subjective career success (SCS), and career commitment (CC). In this study, work value support is classified as intrinsic work value support (IWVS) and extrinsic work value support (EWVS). A survey method is employed to collect 252 usable questionnaires from public servants of the Central Bureau of Statistics in West Sumatera. The Smart PLS path analysis model is used to assess the measurement model and structural model. This study found that only IWVS had a significant positive impact on SCS. The results also indicate that career commitment is a partial mediating between IWVS and subjective SCS. Interesting findings show that CC is fully mediating the relation between EWVS and SCS. This finding may be used to help practitioners understand the various perspectives on career success and formulate career management policies to maintain and support their employee development.